Gut Microbiota, Probiotics, and Their Interactions in Prevention and Treatment of Atopic Dermatitis: A Review - Fang, Zhifeng; Li, Lingzhi; Zhang, Hao; Zhao, Jianxin; Lu, Wenwei; Chen, Wei (Frontiers in Immunology, 2021)
Atopic dermatitis (AD) is a public health concern and is increasing in prevalence in urban areas. Recent advances in sequencing technology have demonstrated that the development of AD not only associate with the skin microbiome but gut microbiota. Gut microbiota plays an important role in allergic diseases including AD. The hypothesis of the “gut-skin” axis has been proposed and the cross-talk mechanism between them has been gradually demonstrated in the research. Probiotics contribute to the improvement of the intestinal environment, the balance of immune responses, regulation of metabolic activity. Most studies suggest that probiotic supplements may be an alternative for the prevention and treatment of AD. This study aimed to discuss the effects of probiotics on the clinical manifestation of AD based on gut microbial alterations. Here we reviewed the gut microbial alteration in patients with AD, the association between gut microbiota, epidermal barrier, and toll-like receptors, and the interaction of probiotics and gut microbiota. The potential mechanisms of probiotics on alleviating AD via upregulation of epidermal barrier and regulation of immune signaling had been discussed, and their possible effective substances on AD had been explored. This provides the supports for targeting gut microbiota to attenuate AD.